Perovskite light absorption layer, method for simultaneously improving crystallization and carrier transport of perovskite light absorption layer and application of perovskite light absorption layer

By using organic alkali and acid semiconductor molecules in perovskite solar cell materials for acid-base neutralization reaction, the defects in the material crystallization process are solved, carrier transmission capacity is improved, and the photoelectricity of perovskite solar cells is improved. Performance and stability.

CN119136615APending Publication Date: 2024-12-13RENSHUO SOLAR ENERGY (SUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229410.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing perovskite solar cell materials have material defects and low carrier transmission efficiency during the crystallization process, resulting in poor photoelectric performance.

Method used

Organic alkali and acid semiconductor molecules are used to perform acid-base neutralization reactions, optimize the crystallization process of perovskite materials, and improve the electron or hole transport capability of the material through the carrier transport characteristics of acid semiconductor molecules.

Benefits of technology

A uniform and high-quality perovskite absorbing layer crystallization is achieved, which improves the photoelectric performance and carrier transmission capabilities of perovskite solar cells, reduces material costs, and improves the stability of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136615A_ABST
    Figure CN119136615A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite light absorption layer, a method for improving crystallization and carrier transport of the perovskite light absorption layer and application of the perovskite light absorption layer. The method comprises the following steps: mixing a perovskite precursor solution, an organic alkali and an acidic semiconductor molecule, and carrying out a neutralization reaction between the organic alkali and the acidic semiconductor molecule to obtain a modified perovskite precursor solution; and coating the modified perovskite precursor solution on the surface of a substrate, and carrying out annealing treatment to obtain the perovskite light absorption layer. In the preparation process of the perovskite light absorption layer, the damage of the acid-base property to the perovskite material is weakened through the acid-base neutralization reaction, so that not only can the crystallization process of the large-area perovskite material be optimized, but also the carrier transport performance can be improved, and the high-efficiency perovskite large-area solar cell module is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar material, and specifically relates to a perovskite light absorbing layer, and a method and application for simultaneously improving the crystallization and carrier transmission of the perovskite light absorbing layer. Background Art

[0002] The key step in the preparation process of large-area perovskite materials is the crystallization process of perovskite materials, which determines the crystallization quality of perovskite materials and is ultimately related to the photoelectric performance of large-area perovskite solar cell modules. The main factors that usually affect the crystallization process of large-area perovskite materials include perovskite components and solvents. Under specific perovskite components and solvent conditions, the use of additives is the best and most effective way to improve the crystallization process of perovskite materials. Organic bases play an important role in the preparation of perovskite materials as crystallization auxiliary additives. They can effectively complex with divalent metal cations of Lewis acids, thereby reducing the crystallization rate of perovskite materials. Similarly, the prior art also discloses the use of organic small molecule additives, which can not only reduce the crystallization rate of perovskite materials, but also passivate material defects. However, the alkalinity caused by the addition of a large amount of organic bases easily leads to the deprotonation of organic cations at the A position in the perovskite material and produces material defects. At the same time, the introduction of organic additive materials will affect the conductivity of the perovskite material, thereby affecting the carrier transport characteristics.

[0003] In addition, perovskite itself generates free electron-hole pairs in the working state. Improving the carrier transfer rate of perovskite materials is crucial for efficiently collecting and utilizing the above-mentioned free electron-hole pairs, thereby increasing the output current of perovskite solar cells. Since defects in perovskite materials can easily capture free electron-hole pairs, in order to further improve the carrier transfer rate of perovskite materials, using passivation molecules to improve material defects is an effective strategy. The prior art also discloses that efficient transmission of electrons or holes is achieved by introducing N-type or P-type materials into perovskite materials, but these materials are often mostly inorganic metal oxides and high molecular polymers, and new interface defects will be introduced during the doping process, thus failing to achieve the desired effect.

[0004] Therefore, there is an urgent need to develop a perovskite solar cell that can solve a series of problems existing in the crystallization process of the above-mentioned perovskite material while achieving efficient carrier transport function. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a perovskite light absorbing layer, and a method and application for improving the crystallization and carrier transport of the perovskite light absorbing layer. In the preparation process of the perovskite light absorbing layer, the present invention reduces the damage of acidity and alkalinity to the perovskite material through acid-base neutralization reaction, thereby not only optimizing the crystallization process of large-area perovskite materials, but also improving the carrier transport performance, thereby obtaining a high-efficiency perovskite large-area solar cell module.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for simultaneously improving the crystallization of a perovskite light absorbing layer and carrier transport, the method comprising the following steps:

[0008] A perovskite precursor solution, an organic base and an acidic semiconductor molecule are mixed, and a neutralization reaction occurs between the organic base and the acidic semiconductor molecule to obtain a modified perovskite precursor solution;

[0009] The modified perovskite precursor solution is coated on the surface of the substrate, and the perovskite light-absorbing layer is obtained after annealing.

[0010] In view of the fact that the acidity or alkalinity contained in the commonly used additives in the prior art has a certain degree of destructive effect on the perovskite material, for example, the organic base additive can effectively alleviate the crystallization rate of the perovskite film and improve the crystallization quality of the large-area perovskite film, but the alkalinity of the organic base will cause the A-position organic cation in the perovskite material to be deprotonated, thereby affecting the technical problem of the photoelectric performance of the perovskite solar cell, the present invention adopts organic base and acidic semiconductor molecules at the same time, wherein the presence of the acidic group inhibits the alkalinity of the organic base, and the acid-base neutralization reaction between the two can weaken the damage of the acidity and alkalinity to the perovskite material, especially solves the deprotonation damage of the organic cation at the A-position in the perovskite material by the organic base, so that the perovskite crystallization process can be optimized, thereby achieving uniform and high-quality crystallization, while improving the carrier transport capacity of the perovskite material, and finally improving the photoelectric performance of the perovskite solar cell. In addition, the acidic semiconductor molecule has good carrier transport characteristics and can improve the electron or hole transport capacity of the perovskite material. At the same time, the lone pair of electrons in the acidic semiconductor molecules can also anchor the divalent metal cations, thereby passivating the grain boundary defects. The acidic semiconductor molecules provided by the present invention can interact with the transparent conductive oxide (TCO) substrate, thereby realizing the preparation of the hole transport layer-free perovskite solar cell, saving material costs while improving its performance and stability.

[0011] Preferably, the organic base includes any one of an amine compound, a nitrogen-containing heterocyclic compound, a quaternary ammonium base or a guanidine compound, or a combination of at least two thereof, preferably a guanidine compound.

[0012] Preferably, the amine compound includes any one of methylamine, ethylamine, propylamine, n-butylamine, dimethylamine or diethylamine, or a combination of at least two thereof, preferably dimethylamine.

[0013] Preferably, the nitrogen-containing heterocyclic compound includes any one or a combination of at least two of pyridine, piperidine, pyrimidine or quinoline, preferably pyridine.

[0014] Preferably, the quaternary ammonium base includes any one or a combination of at least two of tetramethylammonium hydroxide, tetramethylammonium hydroxide, 1,1,3,5-tetramethylpiperidinium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide or benzyltrimethylammonium hydroxide, preferably tetramethylammonium hydroxide.

[0015] Preferably, the guanidine compound includes any one of urea, thiourea, imidourea, aminobenzenesulfonylguanidine, creatine or metformin, or a combination of at least two thereof, preferably urea.

[0016] Preferably, the acidic semiconductor molecules include acidic P-type molecules and / or acidic N-type molecules.

[0017] Preferably, the acidic P-type molecule includes any one of carbazolylphosphonic acid, 4-aminobenzylphosphonic acid or p-phenylene diphosphonic acid, or a combination of at least two thereof.

[0018] Preferably, the carbazolyl phosphonic acid includes (2-(9H-carbazol-9-yl)ethyl)phosphonic acid, 2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid, [2-(3,6-dibromo-9H-carbazol-9-yl)ethyl]phosphonic acid, [4-(9H-carbazol-9-yl)butyl]phosphonic acid, [4-(3,6-dibromo-9H-carbazol-9-yl)butyl]phosphonic acid, [4-(3,6 -dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, [6-(3,6-dibromo-9H-carbazole-9-yl)hexyl]phosphonic acid or (6-(9H-carbazole-9-yl)hexyl)phosphonic acid or any one or a combination of at least two thereof, preferably 2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid.

[0019] Preferably, the acidic N-type molecule comprises a fullerene derivative.

[0020] Preferably, the fullerene derivative includes any one or a combination of at least two of [6,6]-phenyl-C61-butyric acid, hyaluronic acid fullerene, glycine fullerene or methionine fullerene, preferably [6,6]-phenyl-C61-butyric acid.

[0021] Preferably, the perovskite precursor solution comprises a perovskite material, and the perovskite material has an ABX3 structure, wherein the A-site ions comprise at least one of cesium ions, methylamine groups or guanidine groups, the B-site ions comprise divalent metal cations, and the X-site ions comprise halogen anions.

[0022] Preferably, the divalent metal cations include lead ions and / or tin ions.

[0023] In the present invention, the X-site ions include halogen anions, such as iodide ions (I - ), bromide ion (Br - ) and chloride ions (Cl - ) or a combination of at least two of them in any proportion.

[0024] In the present invention, the solvent of the perovskite precursor solution can be exemplarily a mixture of one or more solvents capable of dissolving perovskite materials such as N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone or 2-methoxyethanol, and the present invention is not limited thereto.

[0025] In the present invention, the concentration of the perovskite material in the perovskite precursor solution is 0.1 mol / L-2.0 mol / L, for example, it can be 0.1 mol / L, 0.2 mol / L, 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2.0 mol / L, etc.

[0026] Preferably, the molar percentage of the organic base is 0.1-10%, preferably 1%, based on the total molar amount of the B-site ions as 100%, for example, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. The present invention is used to regulate the crystallization process of perovskite by regulating the molar percentage of the organic base to change the coordination with the metal cation. If the molar percentage of the organic base is low, the crystallization process of the perovskite will be accelerated, and vice versa, although the crystallization process of the perovskite can be delayed, the alkalinity of the organic base will cause the A-site organic cation in the perovskite material to be deprotonated.

[0027] Preferably, the molar percentage of the acidic semiconductor molecules is 0.1-10%, preferably 1%, based on the total molar amount of the B-site ions as 100%, for example, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. The present invention regulates the molar percentage of the acidic semiconductor molecules so that the alkalinity of the acidic semiconductor molecules and the organic bases are mutually neutralized, thereby enhancing the carrier transport. If the molar percentage of the acidic semiconductor molecules is low, the alkalinity of the organic base will increase the deprotonation of the A-site organic cations in the perovskite material, thereby reducing the photoelectric properties of the perovskite solar cell.

[0028] In the present invention, the coating method exemplarily includes at least one of a doctor blade coating method, a slit coating method or a spray coating method, and the perovskite precursor solution is coated on a flexible or rigid substrate, and a perovskite light absorbing layer is formed after annealing.

[0029] In the present invention, the perovskite light absorbing layer is prepared by the blade coating or slit coating method, and the coating speed can be 1-1000 mm / s, for example, 1 mm / s, 5 mm / s, 10 mm / s, 50 mm / s, 100 mm / s, 200 mm / s, 300 mm / s, 400 mm / s, 500 mm / s, 600 mm / s, 700 mm / s, 800 mm / s, 900 mm / s, 1000 mm / s, etc. Further, the coating speed is preferably 30 mm / s.

[0030] In the present invention, the auxiliary crystallization method in the preparation process of the perovskite light absorbing layer can exemplarily adopt at least one of the hot plate heating method, air blowing method, vacuum flash evaporation method or anti-solvent method, but is not limited to the above auxiliary crystallization methods.

[0031] In the present invention, the annealing step includes transferring the substrate assisted by crystallization to an environment of 50-150°C (for example, 50°C, 80°C, 100°C, 120°C, 150°C, etc.) for heat treatment for 3-30min (for example, 3min, 5min, 8min, 10min, 15min, 20min, 25min, 30min, etc.) to remove the residual solvent, and finally form a dense and uniform perovskite light absorption layer. If the annealing temperature is high and the time is long, it will have an adverse effect on the photoelectric performance of the perovskite solar cell; if the annealing temperature is low and the time is short, the residual solvent will not be fully removed.

[0032] In a second aspect, the present invention provides a perovskite light absorbing layer, wherein the perovskite light absorbing layer is prepared by the method for simultaneously improving the crystallization and carrier transport of the perovskite light absorbing layer according to the first aspect.

[0033] Further preferably, the perovskite light absorbing layer is a lead-tin blended perovskite light absorbing layer.

[0034] In the present invention, the thickness of the perovskite light absorbing layer is 300-2000nm, for example, it can be 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1200nm, 1500nm, 1800nm, 2000nm, etc.

[0035] In a third aspect, the present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises the perovskite light absorbing layer according to the second aspect.

[0036] In the present invention, the perovskite light-absorbing layer according to the second aspect is applied to a perovskite solar cell to obtain a regular structure perovskite solar cell or a reverse structure perovskite solar cell.

[0037] In the present invention, the perovskite light absorbing layer according to the second aspect can be applied to different areas (0.03-7200cm 2 , for example, it can be 0.03 cm 2 , 0.1cm 2 , 1cm 2 , 5cm 2 , 10cm 2 , 50cm 2 、100cm 2 , 200cm 2 , 500cm 2 , 1000cm 2 , 2000cm 2 、3000cm 2 、4000cm 2 、5000cm 2 、6000cm 2 、7000cm 2 、7200cm 2 Single-junction or stacked perovskite solar cells and their components (etc.).

[0038] In the present invention, the perovskite solar cell further includes a transparent conductive substrate, an electron transport layer and a back electrode.

[0039] In the present invention, the transparent conductive substrate exemplarily includes at least one of an indium tin oxide (ITO) substrate, an indium tungsten oxide (IWO) substrate, a fluorine-doped tin oxide (FTO) substrate, an indium zinc oxide (IZO) substrate or an aluminum-doped zinc oxide (AZO) substrate.

[0040] In the present invention, the material of the electron transport layer exemplarily includes C 60 , C 70 , graphene, PCBM, ICBA, Nb2O5, TiO2, SnO2 or ZnO.

[0041] In the present invention, the material of the back electrode exemplarily includes at least one of gold, silver, copper, titanium, chromium, nickel or aluminum.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The present invention provides a method for simultaneously improving the crystallization and carrier transport of a perovskite light-absorbing layer. The present invention adopts an organic base and an acidic semiconductor molecule at the same time, wherein the presence of an acidic group suppresses the alkalinity of the organic base, and after an acid-base neutralization reaction occurs between the two, the damage of the acid-base to the perovskite material can be weakened, especially the deprotonation damage of the organic base to the A-position organic cation in the perovskite material is solved, so that the perovskite crystallization process can be optimized, thereby achieving uniform and high-quality crystallization, while improving the carrier transport capacity of the perovskite material, and finally improving the photoelectric performance of the perovskite solar cell. In addition, the acidic semiconductor molecule has good carrier transport characteristics, which can improve the electron or hole transport capacity of the perovskite material. At the same time, the lone pair of electrons in the acidic semiconductor molecule can also anchor the divalent metal cation to passivate the grain boundary defects. The acidic semiconductor molecule provided by the present invention can interact with a transparent conductive oxide (TCO) substrate, thereby realizing the preparation of a perovskite solar cell without a hole transport layer, saving material costs while improving its period performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 Schematic diagram of the neutralization reaction between the organic base and the acidic semiconductor molecules in Example 1.

[0045] Figure 2 The current-voltage curve diagram for comparing the performance of the perovskite solar cells assembled in Example 1 and Comparative Example 1 is shown.

[0046] Figure 3 For example 1, the area is 57cm 2 Structural diagram of a single-junction perovskite solar cell module.

[0047] Figure 4 The area provided for Application Example 1 and Comparative Application Example 1 is 57 cm 2 Current-voltage curve of a perovskite solar cell module.

[0048] Figure 5The performance of perovskite solar cells prepared with different contents of urea and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid in Examples 2-3 and Comparative Example 1 is compared. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0050] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0051] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0052] Example 1

[0053] This embodiment provides a method for simultaneously improving the crystallization and carrier transport of the perovskite light absorbing layer. Specifically, urea and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid are used to prepare a large-area narrow-bandgap lead-tin blended perovskite film, and its photovoltaic performance is investigated.

[0054] The method for preparing the narrow bandgap lead-tin blended perovskite film comprises the following steps:

[0055] (1) An ITO transparent conductive glass substrate with a size of 2.5 cm×2.5 cm was scrubbed with deionized water mixed with an ITO cleaning solution, and then ultrasonicated with deionized water, acetone, and isopropanol for 30 min each to obtain a cleaned ITO transparent conductive glass substrate.

[0056] (2) The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with UV ozone for 18 minutes.

[0057] (3) Weigh MA according to the molar ratio in a glove box filled with nitrogen. 0.3 FA 0.7 Pb 0.5 Sn 0.5 I3's perovskite precursor material is based on Pb 2+ Sn 2+ Taking the sum of the molar amounts of 100%, 5% of stannous fluoride (SnF2) is added, as well as 5% of urea and 5% of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid are added, and a neutralization reaction occurs between urea and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid. The reaction diagram is shown in FIG. Figure 1The weighed drugs were dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 1:1, stirred for 1 hour, and a narrow bandgap lead-tin blended perovskite precursor solution with a concentration of 2.2 mol / L was prepared.

[0058] (4) In a glove box, a narrow bandgap lead-tin blended perovskite film was prepared by a blade coating method. The solvent was evaporated with an air knife. The blade coating speed was 30 mm / s, the air pressure of the air knife was 0.4 MPa, the film thickness was 1000 nm, and it was annealed on a hot plate at 90°C for 7 min to obtain a crystallized perovskite light-absorbing layer.

[0059] (5) Thermal evaporation, atomic layer deposition, and thermal evaporation were used to prepare C with a thickness of 30 nm. 60 , 5nm SnO2 and 120nm Cu, which serve as the electron transport layer, hole blocking layer and back electrode of perovskite solar cells, respectively.

[0060] from Figure 2 It can be seen that the photoelectric conversion efficiency of the perovskite solar cell without a hole transport layer prepared in this embodiment is 21.8%.

[0061] Application Example 1

[0062] In this application example, a 57 cm2 perovskite light absorbing layer was prepared according to the above-mentioned deposition method. 2 Perovskite solar cell components, such as Figure 3 As shown, the specific preparation process is as follows:

[0063] (1) ITO transparent conductive glass substrate was prepared by laser scribing P1.

[0064] (2) The ITO transparent conductive glass substrate was scrubbed with deionized water, and then ultrasonicated with deionized water, acetone and isopropanol for 30 min each. The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with ultraviolet ozone for 18 min.

[0065] (3) Using the above-mentioned perovskite light-absorbing layer.

[0066] (4) A layer of C with a thickness of 30 nm was deposited by thermal evaporation. 60 .

[0067] (5) Tin dioxide (SnO2) with a thickness of 60 nm is deposited by atomic layer deposition (ALD).

[0068] (6) Prepare P2 using laser scribing.

[0069] (7) A layer of Cu with a thickness of 200 nm was deposited by thermal evaporation as the back electrode.

[0070] (8) P3 was prepared using laser scribing.

[0071] from Figure 4 It can be seen that in this application example, the perovskite light absorbing layer is applied to the narrow-bandgap lead-tin blended perovskite solar cell module to achieve a photoelectric conversion efficiency of 19.6%.

[0072] Example 2

[0073] This embodiment provides a method for simultaneously improving the crystallization and carrier transport of the perovskite light absorbing layer. Specifically, urea and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid are used to prepare a large-area narrow-bandgap lead-tin blended perovskite film, and its photovoltaic performance is investigated.

[0074] The method for preparing the narrow bandgap lead-tin blended perovskite film comprises the following steps:

[0075] (1) An ITO transparent conductive glass substrate with a size of 2.5 cm×2.5 cm was scrubbed with deionized water mixed with an ITO cleaning solution, and then ultrasonicated with deionized water, acetone, and isopropanol for 30 min each to obtain a cleaned ITO transparent conductive glass substrate.

[0076] (2) The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with UV ozone for 18 minutes.

[0077] (3) Weigh MA according to the molar ratio in a glove box filled with nitrogen. 0.3 FA 0.7 Pb 0.5 Sn 0.5 I3's perovskite precursor material is based on Pb 2+ Sn 2+ The sum of the molar amounts of 100% was taken as 100%, and 5% of stannous fluoride (SnF2) was added, as well as 1% of urea and 1% of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid. The weighed drugs were dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 1:1, stirred for 1 hour, and prepared into a narrow bandgap lead-tin blended perovskite precursor solution with a concentration of 2.2 mol / L.

[0078] (4) In a glove box, a narrow bandgap lead-tin blended perovskite film was prepared by a blade coating method. The solvent was evaporated with an air knife. The blade coating speed was 30 mm / s, the air pressure of the air knife was 0.4 MPa, the film thickness was 1000 nm, and it was annealed on a hot plate at 90°C for 7 min to obtain a crystallized perovskite light-absorbing layer.

[0079] (5) Thermal evaporation, atomic layer deposition, and thermal evaporation were used to prepare C with a thickness of 30 nm.60 , 5nm SnO2 and 120nm Cu, which serve as the electron transport layer, hole blocking layer and back electrode of perovskite solar cells, respectively.

[0080] Application Example 2

[0081] In this application example, a 57 cm2 perovskite light absorbing layer was prepared according to the above-mentioned deposition method. 2 The specific preparation process of perovskite solar cell components is as follows:

[0082] (1) ITO transparent conductive glass substrate was prepared by laser scribing P1.

[0083] (2) The ITO transparent conductive glass substrate was scrubbed with deionized water, and then ultrasonicated with deionized water, acetone and isopropanol for 30 min each. The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with ultraviolet ozone for 18 min.

[0084] (3) Using the above-mentioned perovskite light-absorbing layer.

[0085] (4) A layer of C with a thickness of 30 nm was deposited by thermal evaporation. 60 .

[0086] (5) Tin dioxide (SnO2) with a thickness of 60 nm is deposited by atomic layer deposition (ALD).

[0087] (6) Prepare P2 using laser scribing.

[0088] (7) A layer of Cu with a thickness of 200 nm was deposited by thermal evaporation as the back electrode.

[0089] (8) P3 was prepared using laser scribing.

[0090] Example 3

[0091] This embodiment provides a method for simultaneously improving the crystallization and carrier transport of the perovskite light absorbing layer. Specifically, urea and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid are used to prepare a large-area narrow-bandgap lead-tin blended perovskite film, and its photovoltaic performance is investigated.

[0092] The method for preparing the narrow bandgap lead-tin blended perovskite film comprises the following steps:

[0093] (1) An ITO transparent conductive glass substrate with a size of 2.5 cm×2.5 cm was scrubbed with deionized water mixed with an ITO cleaning solution, and then ultrasonicated with deionized water, acetone, and isopropanol for 30 min each to obtain a cleaned ITO transparent conductive glass substrate.

[0094] (2) The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with UV ozone for 18 minutes.

[0095] (3) Weigh MA according to the molar ratio in a glove box filled with nitrogen. 0.3 FA 0.7 Pb 0.5 Sn 0.5 I3's perovskite precursor material is based on Pb 2+ Sn 2+ The sum of the molar amounts of 100% is taken as 100%, and 5% of stannous fluoride (SnF2) is added, as well as 10% of urea and 10% of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid. The weighed drugs are dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 1:1, stirred for 1 hour, and a narrow bandgap lead-tin blended perovskite precursor solution with a concentration of 2.2 mol / L is prepared.

[0096] (4) In a glove box, a narrow bandgap lead-tin blended perovskite film was prepared by a blade coating method. The solvent was evaporated with an air knife. The blade coating speed was 30 mm / s, the air pressure of the air knife was 0.4 MPa, the film thickness was 1000 nm, and it was annealed on a hot plate at 90°C for 7 min to obtain a crystallized perovskite light-absorbing layer.

[0097] (5) Thermal evaporation, atomic layer deposition, and thermal evaporation were used to prepare C with a thickness of 30 nm. 60 , 5nm SnO2 and 120nm Cu, which serve as the electron transport layer, hole blocking layer and back electrode of perovskite solar cells, respectively.

[0098] Application Example 3

[0099] In this application example, a 57 cm2 perovskite light absorbing layer was prepared according to the above-mentioned deposition method. 2 The specific preparation process of perovskite solar cell components is as follows:

[0100] (1) ITO transparent conductive glass substrate was prepared by laser scribing P1.

[0101] (2) The ITO transparent conductive glass substrate was scrubbed with deionized water, and then ultrasonicated with deionized water, acetone and isopropanol for 30 min each. The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with ultraviolet ozone for 18 min.

[0102] (3) Using the above-mentioned perovskite light-absorbing layer.

[0103] (4) A layer of C with a thickness of 30 nm was deposited by thermal evaporation. 60 .

[0104] (5) Tin dioxide (SnO2) with a thickness of 60 nm is deposited by atomic layer deposition (ALD).

[0105] (6) Prepare P2 using laser scribing.

[0106] (7) A layer of Cu with a thickness of 200 nm was deposited by thermal evaporation as the back electrode.

[0107] (8) P3 was prepared using laser scribing.

[0108] Example 4

[0109] The difference between this embodiment and embodiment 1 is that Pb 2+ Sn 2+ The sum of the molar amounts is taken as 100%, 5% of dimethylamine and 5% of [6,6]-phenyl-C61-butyric acid are added in step (3), and the rest are the same as in Example 1.

[0110] Application Example 4

[0111] The difference between this application example and application example 1 is that dimethylamine and [6,6]-phenyl-C61-butyric acid are added in step (3), and the rest is the same as application example 1.

[0112] Example 5

[0113] The difference between this embodiment and embodiment 1 is that in step (3), Pb 2+ Sn 2+ The sum of the molar amounts of is 100%, 0.1% of urea and 0.1% of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid are added, and the rest are the same as in Example 1.

[0114] Application Example 5

[0115] The difference between this application example and application example 1 is that in step (3), Pb 2+ Sn 2+ The sum of the molar amounts is taken as 100%, 0.1% of urea and 0.1% of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid are added, and the rest are the same as in Application Example 1.

[0116] Comparative Example 1

[0117] The difference between this comparative example and Example 1 is that urea and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid are not added in step (3), and the rest are the same as Example 1.

[0118] Comparative application example 1

[0119] The difference between this comparative application example and application example 1 is that urea and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid are not added in step (3), and the rest are the same as application example 1.

[0120] Comparative Example 2

[0121] The difference between this comparative example and Example 1 is that Pb 2+ Sn 2+ The sum of the molar amounts is taken as 100%, and in step (3), only 10% of urea is added in molar percentage, and the rest is the same as in Example 1.

[0122] Comparative Application Example 2

[0123] The difference between this comparative application example and application example 1 is that only urea is added in step (3), and the rest is the same as application example 1.

[0124] Comparative Example 3

[0125] The difference between this comparative example and Example 1 is that Pb 2+ Sn 2+ The sum of the molar amounts is taken as 100%, and in step (3), only 10% of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid is added, and the rest is the same as in Example 1.

[0126] Comparative Application Example 3

[0127] The difference between this comparative application example and application example 1 is that only (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid is added in step (3), and the rest is the same as in application example 1.

[0128] The perovskite solar cells in the above embodiments and comparative examples were tested using a solar cell testing system, and the test results are shown in Table 1:

[0129] Table 1

[0130]

[0131]

[0132] As can be seen from Table 1, compared with Comparative Examples 1-3, Examples 1-5 provided by the present invention simultaneously use an organic base and an acidic semiconductor molecule, wherein the presence of the acidic group suppresses the alkalinity of the organic base, and the acid-base neutralization reaction between the two can weaken the damage of the acidity and alkalinity to the perovskite material, especially solving the deprotonation damage of the organic base to the A-position organic cation in the perovskite material, thereby optimizing the perovskite crystallization process, thereby achieving uniform and high-quality crystallization, while improving the carrier transport capacity of the perovskite material, and ultimately improving the photoelectric performance of the perovskite solar cell.

[0133] from Figure 5 It can be seen that compared with Comparative Example 1 in which no urea and (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid were added, the perovskite solar cell assembled in Example 2-3 of the present invention has a higher photoelectric conversion efficiency.

[0134] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for simultaneously improving the crystallization of a perovskite light-absorbing layer and carrier transport, characterized in that: The method comprises the following steps: A perovskite precursor solution, an organic base and an acidic semiconductor molecule are mixed, and a neutralization reaction occurs between the organic base and the acidic semiconductor molecule to obtain a modified perovskite precursor solution; The modified perovskite precursor solution is coated on the surface of the substrate, and the perovskite light-absorbing layer is obtained after annealing.

2. The method according to claim 1, characterized in that The organic base includes any one of an amine compound, a nitrogen-containing heterocyclic compound, a quaternary ammonium base or a guanidine compound, or a combination of at least two thereof, preferably a guanidine compound.

3. The method according to claim 2, characterized in that The amine compound includes any one of methylamine, ethylamine, propylamine, n-butylamine, dimethylamine or diethylamine, or a combination of at least two thereof, preferably dimethylamine; The nitrogen-containing heterocyclic compound includes any one or a combination of at least two of pyridine, piperidine, pyrimidine or quinoline, preferably pyridine; The quaternary ammonium base includes any one or a combination of at least two of tetramethylammonium hydroxide, tetramethylammonium hydroxide, 1,1,3,5-tetramethylpiperidinium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide or benzyltrimethylammonium hydroxide, preferably tetramethylammonium hydroxide; The guanidine compound includes any one of urea, thiourea, imidourea, aminobenzenesulfonylguanidine, creatine or metformin, or a combination of at least two thereof, preferably urea.

4. The method according to claim 1, characterized in that: The acidic semiconductor molecules include acidic P-type molecules and / or acidic N-type molecules.

5. The method according to claim 4, characterized in that: The acidic P-type molecule includes any one or a combination of at least two of carbazolylphosphonic acid, 4-aminobenzylphosphonic acid or p-phenylene diphosphonic acid; The carbazolyl phosphonic acid includes (2-(9H-carbazol-9-yl)ethyl)phosphonic acid, 2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid, [2-(3,6-dibromo-9H-carbazol-9-yl)ethyl]phosphonic acid, [4-(9H-carbazol-9-yl)butyl]phosphonic acid, [4-(3,6-dibromo-9H-carbazol-9-yl)butyl]phosphonic acid, [4-(3,6-dibromo-9H-carbazol-9-yl)butyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl ...bromo-9H-carbazol-9-yl)butyl]phosphonic acid, [4-(3,6-dibromo-9H-carbazol-9-yl)ethyl]phosphonic acid, [4-(3,6-dibromo-9H-carbazol Any one or a combination of at least two of [methoxy-9H-carbazole-9-yl)butyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, [6-(3,6-dibromo-9H-carbazole-9-yl)hexyl]phosphonic acid or (6-(9H-carbazole-9-yl)hexyl)phosphonic acid, preferably 2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid; The acidic N-type molecules include fullerene derivatives; The fullerene derivative includes any one of [6,6]-phenyl-C61-butyric acid, hyaluronic acid fullerene, glycine fullerene or methionine fullerene, or a combination of at least two thereof, preferably [6,6]-phenyl-C61-butyric acid.

6. The method according to claim 1, characterized in that The perovskite precursor solution includes a perovskite material, and the perovskite material has an ABX3 structure, wherein the A-site ions include at least one of cesium ions, methylamine groups or guanidine groups, the B-site ions include divalent metal cations, and the X-site ions include halogen anions; The divalent metal cations include lead ions and / or tin ions.

7. The method according to claim 6, characterized in that Based on the total molar amount of the B-site ions as 100%, the molar percentage of the organic base is 0.1-10%, preferably 1%; Based on the total molar amount of the B-site ions as 100%, the molar percentage of the acidic semiconductor molecules is 0.1-10%, preferably 1%.

8. A perovskite light absorbing layer, characterized in that: The perovskite light absorbing layer is prepared by the method for simultaneously improving the crystallization and carrier transport of the perovskite light absorbing layer according to any one of claims 1 to 7.

9. The perovskite light absorbing layer according to claim 8, characterized in that: The perovskite light absorbing layer is a lead-tin mixed perovskite light absorbing layer.

10. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the perovskite light-absorbing layer according to claim 8 or 9.